The clinical effects of somatotype difference on isokinetic knee muscle strength and dynamic balance scores (vol 64, pg 28, 2018) - Senol, Deniz; Ozbag, Davut; Kafkas, Muhammed Emin; Acak, Mahmut; Baysal, Ozlem; Kafkas, Armagan Sahin; Ogeturk, Murat (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2020)
[Abstract Not Available]